Cercada pela graça e a serviço do amor: Relato de minha jornada com Deus na graduação em medicina - Penedo, Júlia Miranda (Universidade Federal de São Carlos, 2024)
This Final Course Assignment is part of the Pedagogical Project of the Medical Course at the Federal University of São Carlos. It is a critical-reflective Narrative based on my life experience so far, focusing on the perceptible grace of God throughout my journey, especially during the last 6 years of studying Medicine. The narrative addresses my experiences with Medicine since I was a child, focusing on the activities developed during my undergraduate studies in each of the three cycles that make up the course curriculum, highlighting my experience and learning in each of them, as well as other aspects that were part of my story between the years 2019 and 2024. In addition, the work also brings reports about my experience with “MedCélula”, a Christian group founded to help medical students grow together as medical students in the knowledge of who God is and who we are in Him. Furthermore, it comprises a final section, which includes deep reflections on what Medicine is, who God is, and how Medicine serves and is part of the grace and goodness of our Lord.
Surrounded by grace and in service of love: an account of my journey with God during medical school graduation
Keywords: Medicina; Prática profissional; Educação médica; Espiritualidade; Bíblia; Medical education; Medicine; Professional practice; Spirituality; Bible; CIENCIAS DA SAUDE::MEDICINA::CLINICA MEDICA